Veterans in Ruins: The Soldier’s Impossible Homecoming in Tim O’Brien’s The Things They Carried - Lucie Jammes (Transatlantica)
The notion of homecoming is the focal point of Tim O’Brien’s short story “Speaking of Courage,” which presents an irreconcilable scission between the present and the soldier’s past self and life, before the war. This cleavage is mainly embodied in the landscape of the story: the city that was once familiar seems remote after his homecoming. The way in which the protagonist looks at his hometown while driving around the lake that constitutes its center point allows the gradual (re)appearance of Vietnam landscapes and events in the descriptions, until memories from the past and visions of the present superimpose completely—thereby blurring the boundaries between war and peace, between suburban America and Vietnam battlegrounds. The bedimming of differences between the structural polarities of the “here” and the “elsewhere” enables the emergence of paradoxical esthetics based on the notions of conflation and reversal, which thwart the prospect of ever returning home by rendering the very notion of return nonsensical and unachievable. Through writing, O’Brien thus puts into question the very possibility and completeness of the soldier’s homecoming by collapsing together different spatiotemporal realities.